Prevalence of Gastroesophageal Reflux Disease and Its Impact on Quality of Life Among Medical Undergraduates at the University of Jaffna, Sri Lanka - Manori Vijaya Kumari (Journal of Tropical Health, 2026)
Introduction: Gastroesophageal reflux disease (GERD) may affect student well-being and daily functioning. Medical undergraduates may be vulnerable to GERD because of academic stress, irregular meal patterns, and lifestyle factors. However, limited data exist on its prevalence and its impact on the quality of life in this group. This study aimed to determine the prevalence of GERD and its impact on the quality of life among medical undergraduates.Methods: A cross-sectional study was conducted among medical undergraduates at the University of Jaffna, Sri Lanka. The validated GerdQ questionnaire was self-administered to identify individuals with symptomatic GERD, and quality of life was assessed using the GERD-specific quality of life questionnaire.Results: Among 691 medical undergraduates, the prevalence of symptomatic GERD was 26.9%, with heartburn being the most common symptom. Missing meals was significantly associated with symptomatic GERD (adjusted OR 1.73, 95% CI 1.23–2.45, p=0.002). Quality of life was significantly lower among students with GERD (mean=65.94 ± 25.77) compared with those without GERD (mean=84.79 ± 21.24, p